Promoting students’ metacognitive activities through TGfU - Chatzipanteli Αθανασία; Diggelidis Νικόλαος (Inquiries in Physical Education and Sport, 2012)
The aim of the study was to examine the effectiveness of the TGfU model in promoting metacognitive activity in basketball. TGfU is a tactical-skill approach to teaching games in which the participants are learning though playing the games. Seventy-three students aged 11 years old children participated in the study. Students were divided into two groups: i) the experimental group consisted of 29 students and ii) the control group of 44 students. Teachers in the intervention classes applied the tactical-game approach (TGfU) but in the control group no intervention applied. Metacognition was assessed pre and postintervention using a metacognitive questionnaire (Theodosiou & Papaioannou, 2006). Repeated measures analysis showed that there were statistically significant differences between groups. The results imply that the tactical-game approach is an effective way to improve metacognitives activities in physical education classes.